The Economic Implications of Sociodemographic Moderation on the Relationship Between Ethical Morals, Knowledge, and Tax Avoidance - Prasetiyo, Heri; Darma, Gede Sri (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the role of age, gender, and income in moderating the relationship between ethical morals and knowledge on tax avoidance. The research design uses a quantitative approac. Data collection involves primary data with a questionnaire instrument using a semantic differential scale with a 10-point score. The respondents in this study are MSME (Micro, Small, and Medium Enterprises) actors in the KPP Pratama Badung Utara region, totaling 130 individuals. Data is analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results show that, directly, ethical morals and knowledge have a positive and significant impact on tax avoidance. Age does not significantly moderate the relationship between ethical morals and knowledge on tax avoidance. Gender does not significantly moderate the relationship between ethical morals and knowledge on tax avoidance. Income does not significantly moderate the relationship between ethical morals and knowledge on tax avoidance.